HUBUNGAN POLA PENGGUNAAN LAHAN TERHADAP INDEKS BAHAYA EROSI DI SUB DAS SOPU BAGIAN HULU KABUPATEN POSO PROPINSI SULAWESI TENGAH - Bunga Alim Somba (Universitas Tadulako, 2006)
Objectives of this research were to measure effects of land use types and physical environmental condition toward level of erosion hazard as indicators on watershed management. Using survey and non experimental approaches, this research was conducted on September to December 2005. Applying quantitative model such us Universal Soil Loss Equation (USLE) and stepwise regression procedure, it was found that on open land (with more than 15 % slope steepness) and plantation area (with more than 40 % slope steepness) were significantly increasing actual erosion to 4.005 t/ha/thn and 2.807 t/ha/thn. Moreover erosion hazard index for open land was 99 t/ha/year and for plantation area was 81,78 t/ha/year in which categorized as medium level. Most of the land use types contributed the amount erosion more than tolerance level (34,33 t/ha/year – 44,67 t/ha/year). The influenece of open land and plantatation area variables on increasing erosion hazard were 3.39 and 0.592 times more than their unit areas respectively with determinan coeficien (R2) was 0,88.